Teknologi Tepat Guna PELATIHAN KETRAMPILAN MEMBUAT POT UNTUK ANAK - Iqbal Maimun Umar; Joni Nur Budi (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
In this pandemic era, most of the activities are done around the house, to fill the activities the children can take part in pot-making skills training. The expected benefit is to grow children's motor creativity more actively so that they can produce hand movements that produce artistic works. In addition, activities during the pandemic will benefit children further to develop self-confidence and become entrepreneurial skills.